2016
DOI: 10.2147/copd.s97665
|View full text |Cite
|
Sign up to set email alerts
|

Whakawhanaungatanga: the importance of culturally meaningful connections to improve uptake of pulmonary rehabilitation by Māori with COPD – a qualitative study

Abstract: BackgroundPulmonary rehabilitation is known to improve function and quality of life for people with chronic obstructive pulmonary disease (COPD). However, little research has been conducted on the influence of culture on experiences of pulmonary rehabilitation. This study examined factors influencing uptake of pulmonary rehabilitation by Māori with COPD in New Zealand.MethodGrounded theory nested within kaupapa Māori methodology. Transcripts were analyzed from interviews and focus groups with 15 Māori and ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 35 publications
3
70
0
Order By: Relevance
“…Given the higher incidence of COPD in Indigenous Australian and New Zealand communities, it is important that Indigenous patients with COPD have access to PR. One barrier to attendance at PR may be the lack of attention to cultural needs within mainstream programmes . Currently in Australia, no PR programmes are specifically designed to accommodate the cultural needs of Aboriginal and Torres Strait Islander Peoples and there is little empirical data on what these needs are.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the higher incidence of COPD in Indigenous Australian and New Zealand communities, it is important that Indigenous patients with COPD have access to PR. One barrier to attendance at PR may be the lack of attention to cultural needs within mainstream programmes . Currently in Australia, no PR programmes are specifically designed to accommodate the cultural needs of Aboriginal and Torres Strait Islander Peoples and there is little empirical data on what these needs are.…”
Section: Discussionmentioning
confidence: 99%
“…Currently in Australia, no PR programmes are specifically designed to accommodate the cultural needs of Aboriginal and Torres Strait Islander Peoples and there is little empirical data on what these needs are. In New Zealand, PR programmes provided for Māori individuals by Māori organizations have identified that attendance is enhanced by the opportunity to make culturally meaningful connections with other patients and staff within the programme, having culturally appropriate information available and communicating in a common Māori language . It is imperative that greater efforts are made to ensure safe cultural environments for the delivery of PR, either by Indigenous health professionals providing the PR programmes or by mainstream programmes providing a culturally appropriate environment to encourage and maintain attendance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 This audit confirmed that Māori and Pacific Island patients attended significantly fewer sessions, even with the extra support of Whanau Care Services. Levack et al have recently explored factors influencing uptake of PR by Māori with COPD in New Zealand, 23 concluding that, to improve uptake, PR programs should consider cultural responsiveness and indigenous leadership.…”
mentioning
confidence: 99%
“…Non-white British people were under-represented among pulmonary rehabilitation participants in England and Wales compared with the general population 13. Similarly, indigenous people are nearly absent from pulmonary rehabilitation programmes and associated research,14 yet have health disparity beyond what is associated with socioeconomic status alone. Barriers to implementation of pulmonary rehabilitation here include staffing, resourcing and sustainability of programmes in rural and remote settings15 along with addressing cultural meaning and relevance for indigenous participants 14 15…”
mentioning
confidence: 99%